(untitled) (Communications in Computational Physics, 2008)
A1-Dlinear gyrokinetic code called AWECS is developed to study the kinetic excitation of Alfvénic instabilities in a high-β tokamak plasma, with β being the ratio of thermal to magnetic pressure. It is designed to describe physics associated with a broad range of frequencies and wavelengths. For example, AWECS is capable of simulating kinetic ballooning modes, Alfvénic ion-temperature-gradient-driven modes, as well as Alfvén instabilities due to energetic particles. In addition, AWECS may be used to study drift-Alfvén instabilities in the low-β regime. Here, the layout of the code and the numerical methods used are described. AWECS is benchmarked against other codes and a convergence study is carried out.